International Monetary Fund Annual Report 2016 Financial Statements. (Annual Report of the Executive Board; Annual Report of the Executive Board, 2016)
This paper outlines that the IMF is exposed to various types of operational and financial risks, including credit, market, liquidity, and income risks. The Executive Board of the IMF has overall responsibility for the establishment and oversight of the IMF's risk management framework. The risk management framework encompasses primarily strategic, financial, and operational risks. As part of this framework, the Advisory Committee on Risk Management (ACRM) has been established to analyze, synthesize, and report on risks. Credit risk on credit outstanding refers to potential losses owing to the failure of member countries to make repurchases. Credit risk is inherent in the IMF's unique role in the international monetary system since the IMF has limited ability to diversify its loan portfolio and generally provides financing when other sources are not available to a member. Measures to help mitigate the IMF's credit risk include policies on access limits, program design, monitoring, and economic policies that members agree to follow as a condition for IMF financing; early repurchase policies; and preventative, precautionary, remedial measures and precautionary balances to cope with the financial consequences of protracted arrears.